PENGARUH KEPEMIMPINAN GURU TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SMP NEGERI 5 ENREKANG - Kasmawati . (Idaarah: Jurnal Manajemen Pendidikan, 2017)
This study aims to Know the leadership of teachers in SMP Negeri 5 Enrekang, to determine the motivation of learners in SMP Negeri 5 Enrekang, to know the leadership of teachers to motivation learners in SMP Negeri 5 Enrekang. The type of research is quantitative. The population in this study were all students in SMP Negeri 5 Enrekang which amounted to 280 people. The sampling technique used is Random Sampling. The instruments used are teacher leadership and scale of learning motivation. Processing techniques and data analysis using descriptive statistical analysis and inferential statistics. Based on the technique of descriptive statistical data analysis, teacher leadership in SMP Negeri 5 Enrekang is in the medium category, and the motivation to study in SMP Negeri 5 Enrekang also in the medium category. Based on the technique of analyzing inferential statistic data obtained p value = 0.000 (p <0.005). This means that there is influence of teacher leadership to motivation learners learn in SMP Negeri 5 Enrekang.